A totally extraperitoneal approach for endoscopic resection of a congenital prepubic sinus through the pubic symphysis - Masahiro Fukuhara; Shun Onishi; Yusuke Yonemura; Tomoe Sato; Satoshi Tsutsumi; Toshio Bandoh; Tohru Utsunomiya; Genshiro Esumi (Surgical Case Reports, 2021)
Abstract Background A congenital prepubic sinus (CPS) is a rare congenital anomaly in which a duct remnant extends from the skin opening near the pubic symphysis to various parts and the lesions are mostly located in the preperitoneal space. The totally extraperitoneal (TEP) approach is an operational method that provides a good field of view for the preperitoneal space. We report the CPS through the pubic symphysis in which complete resection was achieved by a TEP approach. TEP approach was minimally invasive and achieved satisfactory cosmetic outcome. Case presentation We herein report the case of a 13-year-old boy with a fistula opening near the dorsal penis. He was admitted to our hospital due to fever and lower abdominal pain. Abdominal ultrasonography and computed tomography revealed an abscess inside a fistula lumen on the posterior surface of the rectus abdominis muscles in the midline of the lower abdomen. Under a diagnosis of CPS, which was located in the preperitoneal space, endoscopic resection was performed by a totally extraperitoneal approach. After making an umbilical incision, the rectus abdominis muscle was excised outward to expose the preperitoneal space. A single-port system was placed in the preperitoneal space. Three 5-mm-port trocars were inserted. As the preperitoneal cavity was expanded, a sinus connecting to the pubic symphysis was confirmed. The pubic symphysis did not connect with the bladder. Because the fistula was penetrated with the pubic symphysis, the remaining caudal fistula was removed from the body surface with a small spindle-shaped incision around the fistula opening. Finally, the sinus was completely resected, with confirmation from both the cranial side and dorsal side of the pubic symphysis. We were able to perform complete resection of the CPS with good visibility and without any peritoneal damage. There were no intraoperative complications. His postoperative course was uneventful during the 1-year follow-up. Conclusions The TEP approach may be feasible for the resection of a CPS and may allow safe and secure resection due to good visibility, even in pediatric patients.